Generation of Broadband THz Transients via Metallic Spintronic Emitters Driven by 20-fs Pulses at 1030 nm - Weigel, Alexander; Helms, Leon; Buberl, Theresa; Vogel, Tim; Hofer, Christina; Fritsch, Kilian; Sabanes, Natalia Martin; Jakob, Gerhard; Klaui, Mathias; Pronin, Oleg; Kampfrath, Tobias; Saraceno, Clara; et al. (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We explore power and bandwidth scaling for the generation of highly-temporally-confined THz transients from spintronic emitters, driven by the 250-fs and 20-fs pulses of a high-power 28-MHz Yb-based laser, spectrally centered at 1030 nm.
CRIS-Team Scopus Importer:2023-03-27